Evaluasi Manajemen Maâhad Al-Jamiâah Perguruan Tinggi Agama Islam - Jamil, Zawaqi Afdal (TADBIR : Jurnal Studi Manajemen Pendidikan, 2018)
This study aims to obtain scientific information on the achievement and effectiveness of Mahad Al-Jamiah program management. The research method used is evaluative research. Data collection using observation techniques, interviews, questionnaires / questionnaires, and document review. Methods of data analysis using descriptive and qualitative quantitative methods. The results of the research obtained the evaluation results obtained value of each aspect, namely: 1) functionalization of management functions Mahad Al-Jamiah 75.46 good category, 2) 100 curriculum management very good category, 3) mahasantri management 80 categories good, 4) management of facilities and infrastructure 71.42 good category, 5) management of educators and education 60 categories enough, 6) public relations management 0 categories very kuran, and 8) special service management 60 categories enough. The results of this evaluation provide advice to the leadership Mahad Al-Jamiah to run the organizing function that is to formulate and determine the methods and procedures, and select and conduct training and education of educators and educational. Furthermore, it is expected that the leadership of Mahad Al-Jamiah to make contact with the community, financial supervision, and form the committee acceptance mahad students.